NASA's Explorer and Great Space Observatories Programs - Wentz, Katelyn, author 650289; Halverson, Kiana, author 650293 (Delhi, India : College Publishing House, 2012)
The Explorer program is a NASA program that provides flight opportunities for heliophysics and astrophysics investigations from space. The program includes 92 missions since 1958, the latest including two missions flown in 2007, one in 2008, and one in 2009.The Explorer program was the United States first successful attempt to launch an artificial satellite. It began as a U.S. Army proposal to place a scientific satellite into orbit during the International Geophysical Year, however, that proposal was rejected in favor of the U.S. Navy's Project Vanguard. The Explorer program was later reestablished to catch up with the Soviet Union after that nation's launch of Sputnik 1 on October 4, 1957.